NILAI-NILAI PENDIDIKAN KARAKTER DALAM KUMPULAN SYAIR BUNGE JAMBU KARYA SYAZSYA KAYUNG - Nadela, Liony Vidya; Priyadi, Antonius Totok; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This research aims to analyze and interpret the character education values in the poetry collection "Kumpulan Syair Bunge Jambu" by Syazsya Kayung and their implementation in schools. The research method employed in this research is descriptive qualitative with a sociological literary approach. Data sources used is the poetry collection book titled "Kumpulan Syair Bunge Jambu," and the data consist of excerpts or lines derived from the poetry collection using documentary study techniques. The analysis results reveal character education values found in "Kumpulan Syair Bunge Jambu" sourced from emotional cultivation include religiosity, honesty, responsibility, social care, and environmental concern. Values originating from intellectual cultivation encompass creativity, appreciation of achievements, and curiosity. Character education values from physical activities involve independence, hard work, and friendliness/ communicativeness. Values derived from emotional and aesthetic cultivation include tolerance, democracy, love for peace, patriotism, and national spirit.